Aspek Pragmatisme dalam Kebijakan Pintu Terbuka Jerman terhadap Pengungsi Timur Tengah: Solusi Grey Population - Nadia Khansa Salsabila (Jurnal Hubungan Internasional, 2019)
In 2015, refugee crisis that occurred in European Union due to the war inthe Middle East formed the background of Germany’s open-door policy.As it is implemented, this open-door policy attracted several controversieswith strong internal criticism and negative public opinion, but the policystill be maintained. This phenomenon raises questions regarding on thebasis of German legitimacy in maintaining an open-door policy whichhas always highlighted the sides and ideas of humanitarianism. Therefore,this study seeks to see other aspects of Germany’s open-door policyas German foreign policy, namely ‘pragmatism’ based on considerationof demographic issues related to greying population which have a negativeimpact on German’s stability and economic prospects. Based on thesethoughts, the author argues that Germany maintained the open-door policyas a solution to help overcome greying population in demographic andeconomic context. The open-door policy can be use as a solution throughthe use of refugees and immigrants as productive workers and tax payersin Germany.